Faktor Risiko Kejadian Osteoarthritis pada Masyarakat di Wilayah Kerja Puskesmas Lampulo Kota Banda Aceh Tahun 2025 - Cut Muthia Febrina Rizky -; Tahara Dilla Santi; Wardiati Wardiati (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Osteoarthritis is a degenerative joint disease characterized by cartilage damage and often causes disability, especially in the elderly. It is a public health problem due to its reduced quality of life. This study aims to determine the risk factors associated with osteoarthritis in the community within the Lampulo Community Health Center (Puskesmas) in Banda Aceh City in 2025. The study used a descriptive analytical design with a case-control approach. The population comprised the entire community within the Lampulo Community Health Center's working area, using a total population approach, involving 48 case respondents and 48 control respondents. The study was conducted from April 24 to May 21, 2025. Data were collected through interviews using a structured questionnaire and analyzed using the chi-square test in SPSS. Univariate results showed that the majority of respondents were employed (61.5%), had moderate physical activity (44.8%), were obese (54.2%), and had no comorbidities (52.1%). Bivariate analysis showed no significant association between gender, occupation, obesity, and physical activity with osteoarthritis incidence. However, there was a significant association between comorbidities and the incidence of osteoarthritis (P value = 0.000; OR = 25.000). The study's conclusions indicate that comorbidities are a major risk factor for osteoarthritis. Patients are advised to pay attention to risk factors, while community health centers are encouraged to increase education and health promotion related to osteoarthritis prevention.